"In the Grasp of the Pan-Slavic Octopus"*: Hungarian Nation Building in the Shadow of Pan-Slavism Until the 1848 Revolution. Issue 1 (2nd January 2022) - Pál, Judit
Abstract: This study analyzes the impacts that fear of Pan-Slavism had on Hungarian politics and how this fear was politically instrumentalized in the 1840s and during the 1848 Revolution. Pan-Slavism was the best-known image of the enemy and is associated with the fear of the Russian Empire. The fear of Russia and Pan-Slavism permeated the thinking of the Hungarian reform generation, and together with the vision of national death, had an impact on politics. In addition to its impact on nation- and state-building, the fear of Pan-Slavism also served as an argument in favor of socio-political reforms. The Hungarian political elite aspired to create a national state on the French model, and the instrumentalized use of Pan-Slavism was in many cases used to justify measures intended to speed up the formation of a Hungarian national state.